2012
DOI: 10.1111/j.1751-228x.2012.01156.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Is a Natural Cognitive Ability for Humans

Abstract: We suggest that a multidisciplinary approach to teaching has potential to widen its scope. In that vein, we revisit our original claim that teaching is a natural cognitive ability among humans. We elaborate on three requirements for such an ability and report that, first, teaching strategies may be developmentally reliable. Findings indicate a possible normative developmental trajectory from age one year through adulthood. Second, teaching seems to be species‐typical, that is, it is a universal human achieveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
147
1
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(165 citation statements)
references
References 70 publications
7
147
1
6
Order By: Relevance
“…An entire system of instruction has been invented over years to handle this massive challenge in cultural transmission. In WEIRD society, infants are subject to early lessons from conscientious and attendant parents and, not surprisingly, they become precocious teachers themselves 15 (Strauss & Ziv, 2012). Nevertheless, despite spending billions on developing curricula, methods, and teacher training, the schooling process, at least across much 15 My daughter Nadia is nearly two years older than her younger sibling Sonia.…”
Section: Teaching In the Present And Futurementioning
confidence: 99%
“…An entire system of instruction has been invented over years to handle this massive challenge in cultural transmission. In WEIRD society, infants are subject to early lessons from conscientious and attendant parents and, not surprisingly, they become precocious teachers themselves 15 (Strauss & Ziv, 2012). Nevertheless, despite spending billions on developing curricula, methods, and teacher training, the schooling process, at least across much 15 My daughter Nadia is nearly two years older than her younger sibling Sonia.…”
Section: Teaching In the Present And Futurementioning
confidence: 99%
“…This interaction constitutes the minimal core of pedagogy. While neuroscience and cognitive neuroscience have led to a thorough understanding of how we learn, we remain quite ignorant on the cognitive mechanisms of how we teach (Caro & Hauser, 1992;Davis-Unger & Carlson, 2008a, 2008bStrauss & Ziv, 2012;Strauss, 2005;Thornton & Raihani, 2008). Paradoxically, teaching constitutes the most prominent and distinctive vehicle to propagate knowledge in human societies (Csibra & Gergely, 2011;Tomasello & Rakoczy, 2003), and has had a major impact on cementing our culture (Csibra & Gergely, 2011;Posner & Rothbart, 1998;Tomasello, Carpenter, Call, Behne, & Moll, 2005;Tomasello & Rakoczy, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…It has also been shown that the exchange of knowledge between children is initially marked by guidance, with the child teacher regulating the experience and later on becoming a more collaborative behavior (LeBlanc & Bearison, 2004). How and when children engage in teaching was studied in the remarkable seminal work of Strauss and collaborators (Strauss & Ziv, 2012;Ziv & Frye, 2004;Ziv et al, 2008). The authors showed that children as young as age 3 teach effortlessly and spontaneously.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Estas circunstancias han de ser tomadas como un valor pedagógico por parte del maestro, puesto que facilitan el uso de estrategias didácticas y de evaluación más acordes con una atención adecuada a la diversidad existente en la clase; el alumnado de diferentes edades puede ayudarse entre sí, aprender conjuntamente, aprender a aprender y enseñarse mutuamente, confiando en la fiabilidad propia del desarrollo humano (Strauss y Ziv, 2012) en el marco de situaciones sociales semejantes a las que se dan fuera de la escuela (Abós, Boix y Bustos, 2014). La escuela rural además, por sus características contextuales y por el papel que juega en la dimensión territorial, va a ser siempre conceptualizada desde una perspectiva de multigraduación y heterogeneidad, a no ser que cambien de forma radical las políticas educativas en relación al número de alumnos por aula y en el concepto de educación en el que se sustentan las mismas.…”
unclassified